Systematic Share Price Fluctuations after Bankruptcy Filings and the Investors Who Drive Them - Dawkins, Mark C. (Institutional Knowledge at Singapore Management University, 2007)
Beginning in the 1990s, firms often continue to trade on the major national exchanges after Chapter 11 bankruptcy filings. For bankruptcies filed from 1993-2003, we find that the more negative the filing period price reaction, the more favorable the immediate post- filing returns, on average. This reversal is not attributable to bid-ask bounce, it holds after controlling for other factors associated with post-filing returns, and it appears more attributable to the activities of large traders than to small traders. Supplementary tests reveal that the pattern of post-filing returns differs significantly for bankruptcies filed in bull versus bear markets. Bankruptcies filed during the 1993 to 1999 bull market enjoy substantial but short-lived reversals averaging one-third of the filing period price plunge. These reversals are inconsistent with efficient assimilation of the bankruptcy information. In contrast, we find no evidence of post-filing reversals for bankruptcies filed from 2000 to 2003.